ANALISIS KESIAPAN GURU KELAS SEKOLAH DASAR DALAM MENGELOLA PENDIDIKAN INKLUSIF - Warastuti, Wahyu; Wiwin Kurniyanti; Yustina Neny Hastuti; Choiriyah Widyasari; Minsih, Minsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the readiness of classroom teachers in handling children with special needs at SDN 03 Gumeng and to identify the challenges faced in implementing inclusive education. The research method used is in-depth interviews with classroom teachers and field observations to evaluate inclusive education practices. The results of the study indicate that although classroom teachers at SDN 03 Gumeng understand their roles in inclusive education, their readiness to handle children with special needs is still lacking. The main factor influencing this lack of readiness is the absence of special education teachers at the school. Field observations revealed that classroom teachers often struggle to manage children with special needs, evidenced by discriminatory attitudes, lack of individualized education program (IEP) preparation, and inappropriate evaluation techniques. The study also found that classroom teachers' attention is often divided between children with special needs and regular students, resulting in inadequate special guidance for children with special needs. Based on these findings, it is recommended that there be increased training and support for classroom teachers to overcome the challenges faced and the placement of special education teachers at the school to support the more effective implementation of inclusive education.